Institutional quality and the wealth of autocrats - Christopher J Boudreaux; Randall Holcombe (European Journal of Government and Economics (EJGE), 2017)
One frequently given explanation for why autocrats maintain corrupt and inefficient institutions is that the autocrats benefit personally even though the citizens of their countries are worse off. The empirical evidence does not support this hypothesis. Autocrats in countries with low-quality institutions do tend to be wealthy, but typically, they were wealthy before they assumed power. A plausible explanation, consistent with the data, is that wealthy individuals in countries with inefficient and corrupt institutions face the threat of having their wealth appropriated by government, so have the incentive to use some of their wealth to seek political power to protect the rest of their wealth from confiscation. While autocrats may use government institutions to increase their wealth, autocrats in countries with low-quality institutions tend to be wealthy when they assume power, because wealthy individuals have the incentive to use their wealth to acquire political power to protect themselves from a potentially predatory government.
Keywords: 330; Institutional Quality; Wealth; Autocrats